Thermal and spectral properties of di- and trimethoxybenzoates of silver (I) - Dziewulska-Kułaczkowska, Agnieszka; Ferenc, Wieslawa (Eclética Química, 2009)
The complexes of silver(I) with 2,3-, 2,4-, 2,6-, 3,4-, 3,5-dimethoxy-, and 2,3,4- and 3,4,5-trimethoxybenzoic acid anions have been synthesized and characterized by elemental analysis, IR spectroscopy, thermogravimetric and X-ray studies. Their solubility in water has been also determined at 293K. All analysed complexes were found to be crystalline, anhydrous compounds with low symmetry. The carboxylate groups act as bidentate or monodentate ligands. The thermal stability of compounds has been examined in air in temperature range of 293-1173K. The analysed complexes were found to be stable at room temperature and their solubilities in water at 293K to be in the order of 10-4 mol.dm-3.